The concentration and probabilistic health risk assessment of nitrate in Iranian drinking water: a case study of Ilam city. (2nd October 2021) - Gholami, Zeinab; Abtahi, Mehrnoosh; Golbini, Mehdi; Parseh, Iman; Alinejad, Abdolazim; Avazpour, Moayed; Moradi, Samin; Fakhri, Yadolah; Mousavi Khaneghah, Amin
Abstract: In this study, the concentration of nitrate in 11 drinking water points in Ilam city was investigated, and furthermore, the consumer's probabilistic health risk was assessed. The nitrate levels in cumulative probability plot (CPD) of 50% (CEXP50 ) and 95% (CEXP95 ) were calculated as 8.12 and 16.37 mg/L, respectively, while in all samples ( n = 77) were measured as significantly ( ρ value) lower than 50 mg/L (the proposed reference value by the World Health Organization (WHO) as well as Iranian national standard. Considering the probabilistic health risk; Hazard Quotient 50% (HQ50 ) and Hazard Quotient 95% (HQ95 ) were measured as 0.21 and 0.4, (HQ <1), respectively. Based on acceptable daily intake dose, HQ50s for men, women, and children were 0.09, 0.07, and 0.11 while HQ95s were 0.16, 0.12, and 0.22, respectively. Therefore, the order of the Hazard Quotients (HQ50 and HQ95 ) based on the age group of consumers was summarized as children > men > women. The health risk assessment shows that all consumers are safe of health risk.